The Effect of Alternative Bearing Surfaces on the Risk of Revision Due to Infection in Minimally Stabilized Total Knee Replacement: An Analysis of 326, 603 Prostheses from the Australian Orthopaedic Association National Joint Replacement Registry. (17th January 2018) - Vertullo, Christopher J.; Lewis, Peter L.; Peng, Yi; Graves, Stephen E.; de Steiger, Richard N.
Abstract : Background: The effect of alternative bearing materials on the risk of revision due to infection after total knee replacement remains uncertain. By reducing the immunomodulating polyethylene wear-particle burden and with different substrate bacterial adhesion properties, Oxinium oxidized zirconium and cross-linked polyethylene (XLPE) could alter infection risk. The purpose of the current study was to analyze the risk of revision for infection in 3 comparisons of bearing combinations. Methods: To evaluate the risk of revision for infection with XLPE, cobalt-chromium (CoCr) on XLPE was compared with CoCr on non-cross-linked polyethylene (NXLPE). To evaluate Oxinium, Oxinium-NXLPE was compared with CoCr-NXLPE, and to evaluate the possibility of an additional beneficial effect of Oxinium on XLPE, Oxinium-XLPE was compared with CoCr-XLPE. The cumulative percent revision (CPR) and hazard ratio (HR) for revision for infection in primary total knee replacement for osteoarthritis were determined from registry data from September 1, 1999, to December 31, 2015. Revisions within 6 months following the primary surgery were censored from the analysis, while procedures with posterior stabilized or fully stabilized total knee replacements as well as prostheses with a known higher risk of revision were excluded. Analyses were stratified by age, sex, and fixation type. Results: Of the 326, 603 included primary total knee replacements, 1, 511 (0.46%) were revised for infection. The risk of revision for infection was lower for CoCr-XLPE compared with CoCr-NXLPE (HR = 0.74; 95% confidence interval [CI] = 0.65 to 0.84; p < 0.001). This effect was apparent for both male and female patients overall, all fixation types, antibiotic cement use, those <65 years of age, and male patients ≥65 years of age. However, for female patients ≥65 years of age, there was no difference. Overall, Oxinium-NXLPE had the same revision risk as CoCr-NXLPE regardless of fixation; however, for cemented fixation, subanalysis showed a lower risk for Oxinium-NXLPE compared with CoCr-NXLPE (HR = 0.69; 95% CI = 0.51 to 0.94; p = 0.018). Oxinium-XLPE had the same revision risk for infection as CoCr-XLPE overall, among male patients, and when cemented fixation had been used. Conclusions: In this registry analysis, CoCr-XLPE had a 26% lower risk of revision for infection than CoCr-NXLPE, suggesting a reduction of wear particle-induced immunomodulation with XLPE. Oxinium-XLPE had the same risk as CoCr-XLPE. Overall, Oxinium did not reduce the infection risk. Level of Evidence: TherapeuticLevel III . See Instructions for Authors for a complete description of levels of evidence.